Friendship, Depression, and Suicide Attempts in Adults: Exploratory Analysis of a Longitudinal Follow‐Up Study. Issue 6 (17th February 2017) - Marver, Julia E.; Galfalvy, Hanga C.; Burke, Ainsley K.; Sublette, M. Elizabeth; Oquendo, Maria A.; Mann, J. John; Grunebaum, Michael F.
Abstract : Social support is thought to protect against the risk of suicidal behavior in young people and late life, but less is known about the role of friendship in adults. We explored the effect of friendship on suicide attempt risk during 1‐year follow‐up of 132 adults presenting with major depressive episode (MDE). Items from the Social Adjustment Scale–Self‐Report were used as an index of frequency and quality of recent friendship contacts. Survival methods tested associations of friendship with risk of suicide attempt, recurrent MDE, and related outcomes during follow‐up. Impaired friendship predicted greater risk of suicide attempt in an unadjusted Cox model. This association was stronger for quality ( p = .009) than frequency ( p = .081) of friendship contacts. In the adjusted model, the effect of friendship on suicide attempts was largely explained by self‐reported depression severity. Friendship has a potentially bidirectional relationship with depression, and its effect on suicidal behavior appears to occur through its relationship with depression. Future research should examine the effect of antidepressant treatment on friendship and be designed to test mediation models of relationships between friendship, depression, and suicidal behavior.